Manuscritos culinários congregacionais: vozes e escrituras de freiras da cidade de João Pessoa - Ferreira, Alessandra Gomes Coutinho (2010)
Cooking recipes present in culinary manuscripts denote voices embodied in the materiality of signifiers that have become visible and audible in the potentiality of the words that resonate and echo in these texts. The analysis of these voices allows the reconstruction of threads and traces that show the presence of a linguistic memory of a time and space from what was written in simple everyday notes. The study of discursive traditions of these recipes showed what was recorded in the culinary manuscripts; how these writings were organized in notebooks, the way the making of these recipes was described; what has changed and what remained as a spelling record of the time when those recipes were fixed. Thus, the congregation culinary manuscripts are the expression of linguistic memory and the memory of the taste of the religious orders in the city of Joao Pessoa. By understanding those recipes of these orders as a “writing”, for they are the fixation of an oral text, according Zumthor (1993), and by having a story to be told from what used to be eaten, according to the studies of Gilberto Freyre and Camara Cascudo, we will show that the taste preferences are conditioned to the society and the culture that a particular group belongs to, therefore, food transcends the physiological traits, pointing to a social, historical, linguistic and cultural style.